Sachets at the bottom of the pyramid : redesigning laundry detergent sachet packaging systems for impactful reduction of plastic waste in the Philippines : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, New Zealand - Tanaka, Julian (Massey University, 2021)
This project reimagines single-use plastic sachet packaging systems for laundry detergent powder in the Philippines to significantly reduce environmental harm. Sachets are a flexible single-serve packaging which are typically multi-layered, making them almost impossible to recycle. In the Philippines, people at the Bottom Of (the economic) Pyramid depend on sacheted products because it's what they can afford out of their average NZD 2-6 income per day. In the Philippines, 164 million sachets are used every single day. For both Unilever and Procter & Gamble who operate in the Philippines, more than 50% of their market shares are from sachet sales. The Philippines also happens to be ranked at the bottom in world waste management scores. Single-serve, single use and affordable sachets bring many benefits to consumers, small retailers and multi-national corporations, but the harm they create to its consumers and the environment now outweigh those benefits. This research uses different design methods to continue the delivery of affordable goods to the BOP market while eliminating plastic sachets.
Keywords: packaging design; single-serve packaging; single-serve sachet; sachet economy; plastic waste; bottom of pyramid; FMCG; BOP; sachet marketing; sustainable packaging; eco-friendly packaging; plastic waste reduction; 330309 Industrial and product design